Decomposition of meaning in translation of cultural terms in the novel Alfu Laylah Wa Laylah into Indonesian - Fikri, Fikri; Sutrisno, Adi (Diksi, 2023)
The This study is objected to describe the decomposition of meaning that includes distortion, narrowing and expansion as well as omissions in the translation of cultural terms in a novel titled alfu laylah wa laylah along with their impact on target text. This research utilized a descriptive method with a qualitative research approach. The data collection method used in several stages, as follow: 1) reading the entire contents of the novel; 2) identifying; 3) recording and; 4) giving code and page on each data. The data were subsequently analyzed in several steps including 1) classifying the types of cultural terms in the novel; 2) identifying the meaning of cultural terms in source language and target language; 3) comparing two words in source language and target language; 4) interpreting the findings in form of analysis. It was 29 data found, there were seven cultural terms that experience meaning distortion, twelve with narrowing and expansion of meaning, and ten others underwent omission. In conclusion, four factors of information reduction result in loss.